Pahang state folklore based on the legend of Chini Lake dragon - Robe’ah, Yusuf; Fathiah Izzati, Mohammad Fadzillah; Jamilah Bebe, Mohamad; Jamal Rizal, Razali (Universiti Malaysia Pahang, 2022)
This paper discusses the famous Pahang state folklore which is the Legend Dragon of Chini Lake. This state has an extensive forest as well as breathtaking islands. Among the popular attractions are Tioman Island and Chini Lake. Chini Lake is very famous for its stories of dragons in various versions. It is said that the history of Tioman Island started with the tale of the dragon that left Chini Lake. It is believed that the story of the dragon is related to an island in Indonesia. Hence, the name of the villages on the island are similar to the names of the villages on Tioman Island such as Mukut, Genting, Juara, Salang and Paya. Apart from the similarity of the village name, the shape of both islands is also quite similar as both have sharp mountain tops such as dragon horns. The similarity of the name of the village has led to allegations that the residents of Tioman Island are from the Riau Archipelago and Khmer, Cambodia.The allegation states that the residents there are of Cambodian descent because the dialects used have little in common. Nevertheless, this unique qualities demands more in-depth research to be documented to today’s generation.